Evaluation of the ability of health care providers and patients to distinguish different colour shades and accuracy of visual glucose estimation when using colorimetric glucose measurement strips - van Zyl, Danie G. (University of Pretoria, 2026)
Mini Dissertation (MsC (Epidemiology))--University of Pretoria, 2019.